Defective/graphitic synergy in a heteroatom-interlinked-triggered metal-free electrocatalyst for high-performance rechargeable zinc–air batteries. Issue 34 (17th August 2021) - Yasin, Ghulam; Ibrahim, Sehrish; Ibraheem, Shumaila; Ali, Sajjad; Iqbal, Rashid; Kumar, Anuj; Tabish, Mohammad; Slimani, Yassine; Nguyen, Tuan Anh; Xu, Hu; Zhao, Wei
Abstract : A strategy for defective/graphitic synergy in heteroatom-interlinked-triggered asphaltene (D/G-HASP) is presented. D/G-HASP reveals outstanding catalytic activities and durability in half-cell (ORR/OER) and full-cell (zinc–air) reactions. Abstract : Motivated by the increased demand for energy storage technologies with maximum power density and safety, zinc–air batteries have drawn extensive attention. However, developing a competent and robust bifunctional oxygen reduction and oxygen evolution reaction (ORR/OER) catalyst and studying the underlying active-site mechanisms with the aim of optimizing the electrochemical process remains challenging. In this work, defective/graphitic synergy in heteroatom-interlinked-triggered asphaltene (D/G-HASP) is explored via Raman spectroscopy, density functional theory (DFT), and other characterization approaches, in which reactions involving the oxygen-containing intermediates on the carbon substrate can be accelerated by the electron deficit triggered by heteroatoms, thus enhancing the oxygen reaction performance. As estimated, D/G-HASP reveals a superior half-wave potential ( E 1/2 = 840 mV) and the lowest overpotential ( η 10 = 310 mV) towards the ORR and OER compared to its other counterparts. Remarkably, zinc–air batteries primed with such an air-electrode show outstanding reversibility and stability. This effort hence delivers insightful understanding of the synergistic reaction principles of heteroatom-interlinked-triggering nanomaterials when used in zinc–air batteries.